The Effect of Inflation And Interest Rates on The Exchange Rate of The Rupiah In Indonesia From 1993 To 2023 - Efendi, Mesty Asyura; Martilova, Novera; Elmizan, Gina Havieza; Widianita, Rika (Peneliti.net, 2025)
The resulting globalization resulted in interactions between several countries with other countries in various parts of the world, resulting in international trade. In trade between countries, there are differences between countries, namely currency which is one of the characteristics. The benefit of this study is to see whether there is an influence of independent variables on dependent variables. In this study using an approach, this study uses time series data from 1993 to 2023, time series data obtained from the source of the Central Statistics Agency of West Sumatra Province. This study uses several test models including descriptive statistical tests, normality tests, autocorrelation, heteroscedasticity, multicollinearity, multiple linear regression, R² test, t test, and f test. The data obtained were processed using SPSS statistics version 26. The test carried out on the t test has a positive influence on the exchange rate t_calculated (4.577) > t_table (2.048), significant 0.000 <0.05. The test conducted on (X2) found that the interest rate had a negative effect on the exchange rate t_count (4.561) > t_table (2.048), with a significance of 0.000 < 0.05. The results of the f test conducted showed that inflation and interest rates equally affected the interest rate with a t_count value of 11.153 > t_table 3.33, and a significance of 0.00 < 0.005. The test conducted simultaneously using R square 0.443 / 44.3%, the test results together affected the exchange rate by 44.3% which means weak distribution, for 55.7% of 44.3% outside the variables studied.